A multifaceted microenvironment nanoregulator for targeted ovarian cancer therapy - Zu, Yizheng; Li, Min; Li, Ruyue; Ma, Shaohan; Yang, Yu’e; Zhang, Shun; Ma, Yuan; Wu, Tiantian; Ha, Chunfang (Frontiers in Pharmacology, 2025)
The treatment of ovarian cancer is hindered by its insidious onset and rapid progression. Exosomes (EXOs) present a promising therapeutic strategy for ovarian cancer by modulating the tumor microenvironment. However, concerns regarding the biosafety of animal-derived EXOs pose significant challenges to the development of innovative formulations. In this study, we propose a universal strategy to engineer plant-derived EXOs as microenvironment nanoregulators for targeted ovarian cancer therapy. EXOs derived from ginger were purified, loaded with the natural bioactive compound curcumin (Cur) with high encapsulation efficiency, and functionalized with a tumor-targeting aptamer. Upon intravenous administration, the resulting multifaceted microenvironment nanoregulator, termed AGE@Cur, effectively accumulates at the tumor site and exerts a tumor-suppressive effect through remodeling the tumor microenvironment. This novel therapeutic platform not only addresses the limitations of animal-derived EXOs but also paves the way for the development of innovative microenvironment regulators in clinical applications.